2006
DOI: 10.1007/s11042-006-0060-0
|View full text |Cite
|
Sign up to set email alerts
|

Navigation help in 3D worlds: some empirical evidences on use of sound

Abstract: Abstract:The concept of Interaction Locus (IL) has been introduced to help the users to orient, navigate, and identify relevant interaction areas in 3D Virtual Environments (VE). The IL is a multimodal concept: it adds to the 3D visual scene parallel information channels that are perceived by other senses. In particular, the IL emphasizes the role of music as a navigation aid in a VE. This paper reports three user-evaluations of different IL enriched virtual worlds, and in particular of the role of the IL audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Furthermore, case studies show that humans are also able to navigate in virtual acoustic environments based on (3D) auditory cues and beacon sounds [50,51,52,53]. However, fewer studies have investigated the effect of audiovisual presentation on navigation performance [54,55]. Gunther, Kazman, & MacGregor [54] investigated navigation in virtual environments that contained visual objects that could also produce 3D sound.…”
Section: Multisensory Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, case studies show that humans are also able to navigate in virtual acoustic environments based on (3D) auditory cues and beacon sounds [50,51,52,53]. However, fewer studies have investigated the effect of audiovisual presentation on navigation performance [54,55]. Gunther, Kazman, & MacGregor [54] investigated navigation in virtual environments that contained visual objects that could also produce 3D sound.…”
Section: Multisensory Navigationmentioning
confidence: 99%
“…Because the sound was often experienced without the corresponding visual object, multisensory interactions may have played no role in this study. Another study on the effects of multisensory presentation in virtual environments was conducted by Ardito, Costabile, De Angeli and Pittarello [55]. They presented participants with different pieces of classical music in each room of a virtual museum and found that such music could benefit users' navigation and memory performance, but only when users where informed in advance of the link between the music and the rooms.…”
Section: Multisensory Navigationmentioning
confidence: 99%
“…Different studies [2,4,22,31] have focused on sensory information quality within a VE quantifying it via participant's perception instead of only considering technical parameters. In the study presented here, the measure included about participants' perception of delay has shown that their awareness about the existence of mismatches in the sensory cues provided is not directly related with their influence in task performance and the sense of presence.…”
Section: Implications For Human-computer Interaction Designmentioning
confidence: 99%
“…Ardito et al. () used a similar concept but the user was immersed in a VE. Both studies highlight that beneficial methods can be implemented to present useful information to users based on their location; information that may not be readily apparent normally.…”
Section: Literature Review and Rationalementioning
confidence: 99%